2019
DOI: 10.7554/elife.50928
|View full text |Cite
|
Sign up to set email alerts
|

Crl activates transcription by stabilizing active conformation of the master stress transcription initiation factor

Abstract: σS is a master transcription initiation factor that protects bacterial cells from various harmful environmental stresses including antibiotic pressure. Although its mechanism remains unclear, it is known that full activation of σS-mediated transcription requires a σS-specific activator, Crl. In this study, we determined a 3.80 Å cryo-EM structure of an Escherichia coli transcription activation complex (E. coli Crl-TAC) comprising E. coli σS-RNA polymerase (σS-RNAP) holoenzyme, Crl, and a nucleic-acid scaffold.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…Considering that Mtsp17 is a lipid-binding protein and lack of DNA-binding domain, this transcriptional regulator may work in a DNA-contact independent way by protein-protein interactions. Such mechanism has been utilized by Crl in E. coli, which activates transcription by interacting with sigma factor [24]. More investigations are needed to explore the potential interacting protein of Mtsp17 to complete the transcriptional regulatory network of Mtsp17.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that Mtsp17 is a lipid-binding protein and lack of DNA-binding domain, this transcriptional regulator may work in a DNA-contact independent way by protein-protein interactions. Such mechanism has been utilized by Crl in E. coli, which activates transcription by interacting with sigma factor [24]. More investigations are needed to explore the potential interacting protein of Mtsp17 to complete the transcriptional regulatory network of Mtsp17.…”
Section: Discussionmentioning
confidence: 99%
“…As observed for RbpA, Crl facilitates transcription initiation by stabilizing the σ S -RNAP holoenzyme and stimulating RPo formation (Banta et al, 2013;Xu et al, 2019). Two high resolution cryo-EM-based structures of Crl-σ S -RNAP RPo have been recently described (Cartagena et al, 2019;Xu et al, 2019). Cartagena et al, suggested that Crl stabilizes σ S -RNAP by tethering σ S directly to RNAP though contacts with the β -clamp-toe domain (β -CT, residues 144-179).…”
Section: Crlmentioning
confidence: 96%
“…Although Crl does not bind to σ 70 because of the steric clash with σ 70 -NCR (Cartagena et al, 2019) it can activate σ 70 -dependent transcription (Gaal et al, 2006). As observed for RbpA, Crl facilitates transcription initiation by stabilizing the σ S -RNAP holoenzyme and stimulating RPo formation (Banta et al, 2013;Xu et al, 2019). Two high resolution cryo-EM-based structures of Crl-σ S -RNAP RPo have been recently described (Cartagena et al, 2019;Xu et al, 2019).…”
Section: Crlmentioning
confidence: 98%
See 1 more Smart Citation
“…25 Essentially, this observation was consistent with the structure and function of E. coli RpoD: the regions 1 and 2 were responsible for the binding of the RNAP holoenzyme to the typical promoter sequence-10 region, and for forming an open complex favoring initiation and elongation of transcription. 33,34 Designing artificial TFs Compared with the approach of finding the desired TFs from a mutant library generated by random mutagenesis, the advantages of designing TFs are obvious: evaluating the performance of the designed TFs does not depend on the availability of an HTS method. A satisfactory synthetic bacterial TF should be orthogonal to the endogenous promoters of the host's to ensure minimal off-target effects, and the TF should also be friendly to activity re-programming for a wide range of user-specified translation start sites.…”
Section: Employing Compatible Heterogeneous Tfsmentioning
confidence: 99%